Controlling factors of large-scale harmful algal blooms with Karenia selliformis after record-breaking marine heatwaves - Takagi, Satomi; Kuroda, Hiroshi; Hasegawa, Natsuki; Watanabe, Tsuyoshi; Unuma, Tatsuya; Taniuchi, Yukiko; Yokota, Takashi; Izumida, Daisuke; Nakagawa, Toru; Kurokawa, Tadahide; Azumaya, Tomonori (Frontiers in Marine Science, 2022)
Unprecedented, large-scale harmful algal blooms (HABs) dominated by Karenia selliformis occurred off the southeastern coast of Hokkaido, Japan, from late September to early November 2021, about a month after intense and extensive marine heatwaves (MHWs) had subsided. The aims of the present study were to understand the mechanism of development, maintenance, and decay of the HABs as well as to investigate the effect of the MHWs on the HABs. We developed a one-dimensional, lower trophic-level ecosystem model (NEMURO+) to simulate the HABs. The model successfully simulated the 2021 HABs and indicated that their development, maintenance, and decay were controlled primarily by changes of water temperature. Nitrate supply from subsurface layers by seasonal vertical diffusion in autumn also helped to maintain the HABs. Vertical diffusion following MHWs in 2021 contributed to the long duration of the preferred temperature for K. selliformis and the occurrence of pre-bloom of K. selliformis, resulting in preconditioning and accelerating the HABs. However, simulations for normal years (i.e., the climatological mean during 2003–2018) showed that HABs could have occurred, even in the absence of MHWs. The simulations indicated that massive blooms of other phytoplankton species (e.g., diatoms) would not have occurred in 2021, even in the absence of a K. selliformis bloom. The implication was that the HABs in 2021 were the species-specific responses of K. selliformis. The proposed mechanism of the HABs was peculiar to our study area and differed from that previously reported for other K. selliformis blooms. Specifically, the preferred temperature for the HABs of K. selliformis was clearly lower than the previously reported preferred temperature of K. selliformis; thus, the physiological characteristics of the K. selliformis that bloomed in our study area differed from those of other K. selliformis strains. These discoveries provide the first evidence to explain how MHWs affect HABs, and to understand how inter-regional dissimilarities of K. selliformis can lead to large-scale, devastating outbreaks under different oceanographic conditions.